Кримінально-правова та кримінологічна характеристика суб'єкта грубого порушення угоди про працю ( ст. 173 КК України) - Танаджі, В. Г.; Tanadzhi, V. H. (Європейські перспективи. - 2019. - № 2. – С. 126-131, 2019)
Надано аналіз кримінально-правової та кримінологічної характеристик суб’єкта грубого порушення угоди про працю, що дозволить у подальшому розробити дієвий механізм запобігання та протидії злочинним посяганням у сфері трудових відносин.

The article is focused on studying the subject of flagrant violations of the employment agreement (the Art. 173 of the Criminal Code of Ukraine). Criminal and legal features of the subject of a criminal offense stipulated by the Art. 173 of the Criminal Code of Ukraine have been researched. Based on the analysis of judicial practice (about 500 sentences), the author has discovered and thoroughly analyzed criminological characteristics of the subject of flagrant violations of the employment agreement. The objective of the article is to analyze criminological, criminal and legal characteristics of the subject of flagrant violations of the employment agreement, which will further allow to develop an effective mechanism for preventing and counteracting criminal encroachments in the field of labor relations. On the basis of the conducted analysis of a person who committed a socially dangerous act under the Art. 173 of the Criminal Code, the author has concluded that he is characterized by the presence of special education and a high level of intellectual abilities, the age of such persons is usually more than 30 years, and they are predominantly males. The occupation of persons committing flagrant violations of the employment agreement are managerial positions in enterprises, institutions, organizations or entrepreneurial activities, and such persons occupy in society rather high positions. Regarding criminal and legal characteristics of the subject of a criminal offense, it should be noted that besides general there are additional (special) features characterizing the subject of flagrant violations of the employment agreement, namely the availability of organizational and regulatory powers to manage the labor collective and the duty to observe labor legislation, for the violation of which a person may be brought to criminal liability.

Представлен анализ уголовно-правовой и криминологической характеристик субъекта грубого нарушения соглашения о труде, что позволит в дальнейшем разработать действенный механизм предотвращения и противодействия преступным посягательствам в сфере трудовых отношений.
Танаджі, В. Г. Кримінально-правова та кримінологічна характеристика суб'єкта грубого порушення угоди про працю ( ст. 173 КК України) / Танаджі Василь Григорович // Європейські перспективи. - 2019. - № 2. – С. 126-131.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Кримінологія. Criminology. Криминология; Україна. Ukraine. Украина; грубе порушення угоди про працю; gross violation of the labor agreement; грубое нарушение соглашения о труде; кримінальна відповідальність; criminal liability; уголовная ответственность; суб’єкт злочину; subject of the crime; субъект преступления; особа злочинця; person of the criminal; личность преступника